Description of two new species forming a sympatric species pair of Crenicichla (Teleostei: Cichlidae) endemic to the Piray Guazú River in the Paraná River Basin, Misiones, Argentina and belonging to the C. mandelburgeri species complex - Říčan, Oldřich; Piálek, Lubomír; Almirón, Adriana; Casciotta, Jorge (European Journal of Taxonomy, 2023)
Crenicichla is the largest and most widely distributed genus of Neotropical cichlids. The Crenicichla mandelburgeri species complex from the Middle Paraná departs from the ancestral and predominant ecomorphology of the large genus and shows parallel evolution of ecomorphs both within the complex and also to the unrelated C. missioneira species complex from the Uruguay River. Here, we formally describe a new species pair from the C. mandelburgeri species complex that has evolved a parallel morphological and ecological dichotomy to another species pair and also to species in the unrelated C. missioneira species complex. The new species pair is endemic to a single tributary (the Piray Guazú) of the Middle Paraná River where it is sympatric and partly syntopic. Mitochondrial DNA phylogeny shows the two new species as distantly related within the C. mandelburgeri species complex, each with a sister species in the Iguazú rather than in the neighbouring Paraná River tributaries. Nuclear DNA analyses demonstrate their sister-group relationship, which is however complicated by the reticulated origin of one of the new species. We present determination keys for all the currently formally described species of the C. mandelburgeri species complex including the new species described here.